Hydrothermal dolomites in SW Sardinia (Italy) and Cantabria (NW Spain): evidence for late - to post-Variscan widespread fluid-flow events - Boni, Maria; Bechstädt, Thilo; Gasparrini, Marta (Journal of geochemical exploration, 2000)
Epigenetic replacive and saddle dolomitisations, several hundred meters thick, affected Cambrian to Ordovician limestones across large areas (several hundred kilometers) of the SW Sardinian (Italy) mining district, as well as Paleozoic carbonates of the Cantabrian region (Spain). Prior to dolomitisation, the Cambrian limestones of Sardinia underwent ductile deformation and greenschist facies metamorphism. In Cantabria the dolomitisation affected mostly the already folded limestones of the Barcaliente and Valdeteja Fms of Carboniferous age. In both areas it can be assumed that late-Variscan hydrothermal events, which coincided with extensional tectonics, set brine circulation into motion. Dolomitisation may have occurred within circulation cells, which were driven by high heat flow. It is quite likely, that the dolomitisations are indicative of a widespread fluid-flow event that affected most of SW-Europe.